2019
DOI: 10.1371/journal.pone.0213242
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of DSM-5 based diagnostic tool for children with Autism Spectrum Disorder

Abstract: Diagnostic and Statistical Manual of mental disorder-IV (DSM-IV) TR based INCLEN Diagnostic Tool for Autism Spectrum Disorder (INDT-ASD) is an established instrument for the diagnosis of ASD in Indian subcontinent and low-middle income countries (LMIC). The introduction of DSM-5 necessitated revision of existing INDT-ASD tool to incorporate the DSM-5 related changes. This study was undertaken to develop and validate the DSM-5 based All India Institute of Medical Sciences (AIIMS)-Modified-INDT-ASD Tool. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The parent/caregiver-report questionnaire was based closely on a tool specific for identification of ASD in an Indian context (INDT-ASD). Unsurprisingly, scores on this questionnaire significantly differed between all three groups (ASD, ID, TD) in the expected direction, replicating previous reports with the original tool (Gulati et al, 2019;Juneja et al, 2014).…”
Section: Parent/caregiver-report and Interaction Measuressupporting
confidence: 85%
See 1 more Smart Citation
“…The parent/caregiver-report questionnaire was based closely on a tool specific for identification of ASD in an Indian context (INDT-ASD). Unsurprisingly, scores on this questionnaire significantly differed between all three groups (ASD, ID, TD) in the expected direction, replicating previous reports with the original tool (Gulati et al, 2019;Juneja et al, 2014).…”
Section: Parent/caregiver-report and Interaction Measuressupporting
confidence: 85%
“…Behavioural observations may emerge from parent reports of day-to-day activities of the child, or expert observation of social interaction and play. Brief parent-report tools such as the INCLEN Diagnostic Tool for Autism Spectrum Disorder (INDT-ASD) (Juneja et al, 2014), and All India Institute of Medical Sciences (AIIMS)-Modified-INDT-ASD Tool (Gulati et al, 2019) have demonstrated high sensitivity in early screening and diagnosis of ASD in an Indian setting. Accordingly, the START app includes a brief questionnaire for primary caregivers as well as a provision for video-recording a parent/caregiver-child play session.…”
Section: Toolsmentioning
confidence: 99%
“…Careful structured and patient objective status, coupled with an analysis and explanation of behavior, and backed by history, provides a sound base for ASD diagnosis [ 1 ]. Diagnosis based on a structured questionnaire and observation similar to ours has also been applied by other authors [ 14 , 20 ]. In many countries, diagnosis of ASD is made only by experienced pediatricians, pediatric neurologists, clinical psychologists, and other specialists [ 1 ], which saves time and resources and allows early initiation of therapeutic intervention, even when diagnosis is uncertain [ 9 ].…”
Section: Discussionmentioning
confidence: 92%
“…A review of the worldwide practice showed that ASD is presently diagnosed by multidisciplinary teams or by skilled individual specialists—pediatricians, developmental pediatricians, child psychiatrists, psychologists, or others—depending on the healthcare system and the resources of each country [ 1 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all three settings the quality of services is strengthened by the use of formal assessment tools measuring activity and participation in children with a focus on family perspectives during goal setting. India has taken the lead in adopting or creating developmental assessment tools in multiple languages using culturally appropriate material in the South Asian region [31]. Zaman et al invented the famous Ten Questions screen, one of the earliest disability measures developed in Bangladesh [32].…”
Section: Strengthsmentioning
confidence: 99%